Analysis of Factors Affecting the Behavior of Coffee Shop Consumers in Jambi City - Saidin Nainggolan; Emy Kernalis; Della Zulia Carolin (Randwick International of Social Science Journal, 2022)
This study aims to analyze the factors that affect the behavior of coffee shop consumers in Jambi City. This research was conducted at a coffee shop in Jambi City. The selection of the location of this study was carried out by purposive sampling method. The data analysis used is primary data with the Structural Equation Partial Least Square Model (SEM-PLS) approach. The results showed the behavior of coffee shop consumers most who visited the coffee shop expressed agreement with the choice and decision in behaving. As many as 57.5% of consumers revealed that they chose the coffee shop because the price offered is affordable, coffee served quality, and it has a good taste, and 55% stated that they buy coffee in the coffee shop because according to their consumption needs, the coffee sold has a strong freshness, and has many flavor variants. Internal factors negatively affect the behavior of coffee shop consumers but not significantly. External factors have a positive effect on consumer behavior. Internal factors and external factors with variable moderation of coffee shop variables have a significant effect on consumer behavior.